Commemoration of the 1905 Revolution in the Industrial City : The Case of Łódź - Śmiechowski, Kamil (1985– ) (Instytut Historii Polskiej Akademii Nauk, 2022)
The article discusses the current practices of commemorating the 1905 revolution in Łódź. The changes taking place in the city’s memory policy are conditioned both by the loss of memory of the events from a century ago and by changing political factors in the post-transformation period. The city is a paradigmatic example of a post-industrial city in Central and Eastern Europe facing an identity crisis. Narratives formulated ‘from above’ compete with those created ‘from below’. While the former are based on the construction of a utopian, capitalist city of success, the latter claim the history of the people of Łódź. Revitalising the memory of the Revolution of 1905 plays a key role in these negotiations, contributing to a revision of the post-transformation amnesia about the city’s working-class past
p. 67-87
Keywords: collective memory; politics of memory; urban memory; Revolution of 1905; history of Łódź; urban social movements